(5x-7)/3=6

Simple and best practice solution for (5x-7)/3=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-7)/3=6 equation:


x in (-oo:+oo)

(5*x-7)/3 = 6 // - 6

(5*x-7)/3-6 = 0

(5*x-7)/3+(-6*3)/3 = 0

5*x-6*3-7 = 0

5*x-25 = 0

(5*x-25)/3 = 0

(5*x-25)/3 = 0 // * 3

5*x-25 = 0

5*x-25 = 0 // + 25

5*x = 25 // : 5

x = 25/5

x = 5

x = 5

See similar equations:

| -10=5w(2w-4) | | -w^2+7w-12=0 | | -2.1v-2.3=1.2+4.3 | | 2.4=0.8x+3.2 | | 1/3x-2/3=0 | | 5+3x-9=6x-4 | | x=75p+3550 | | 3n+7n=0 | | (K-1)(k-6)= | | S-8/2=3 | | 3(x)-7=83 | | 0=-w^2+4w-3 | | 10t-22=-5(-2t+3) | | -2w=-3w-7 | | 2/3x+3/4=3/5(x-5/8) | | 5(2x+3)-6+6-3(3x-1)-8=x+10 | | 4n-2.8=6.8 | | 10x+4=6x+8 | | 2x^2+23x-9.5=0 | | 0.06x=0.036 | | 2m+8.1=16.5 | | -3(4p+5)=-99 | | 4/m=10/15 | | 8y-6=-6 | | 9/2(n-85) | | 4c/8c | | C-3/2=2 | | 0.6x-11=2.2x-19 | | m/9=-8 | | 42=40-8(-1-3w) | | -2r(6-2r)/5 | | 0.2x=1.4 |

Equations solver categories